WORKSHOP PENGEMBANGAN KOMPETENSI GURU PAI DALAM PENERAPAN LITERASI KEAGAMAAN DI SEKOLAH - Taufik Helmi; Miftah Ulya; Nurliana; Abdul Rahman; Baktiar Nasution; Febri Giantara (DEVELOPMENT: Journal of Community Engagement, 2025)
This community service program aims to enhance the competence of Islamic Religious Education (PAI) teachers in implementing religious literacy in schools through a workshop activity. The background of this program is rooted in the fact that religious literacy plays a crucial role in shaping students’ religious character, yet it has not been fully integrated effectively into the learning process. The implementation method consisted of three stages: preparation (needs analysis and module development), workshop activities (lectures, discussions, simulations, and microteaching), and evaluation through pre-test, post-test, observation, and questionnaires. The results of the program indicated a significant improvement in teachers’ understanding and skills regarding the concepts and strategies of religious literacy implementation. In addition, workshop participants successfully developed follow-up plans to integrate religious literacy into classroom teaching. Therefore, this workshop proved effective in developing the competence of PAI teachers and in fostering a culture of religious literacy within the school environment.